Research Contributions of Pakistani LIS Scholars: A review of SCOPUS databas - Abid Hussain , Muhammad Ismail & Muhammad Usman (IJoLIS, 2024)
Purpose: The purpose of this study is to present bibliometric analysis of the SCOPUS database and to highlight research contributions of Pakistani Library and Information Science scholars covering the period 1985 to 2022. Design/methodology/approach: The paper is based on quantitative analysis of a total of 197 articles of Pakistani LIS scholars retrieved from Scopus Database.